PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS DENGAN MENGGUNAKAN PENDEKATAN DISCOVERY LEARNING PADA SISWA SEKOLAH DASAR - Risma Tri Nanda; Fadhilaturrahmi; Yenni Fitra Surya; Sumianto; Iis Aprinawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low mathematical critical thinking skills of students in Mathematics lessons in class III B UPT SDN 004 Salo. One solution to overcome this problem is to apply the Discovery Learning learning approach. The purpose of this research is to improve students' mathematical critical thinking skills in Mathematics lessons. The research method is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, and reflection. The research time was carried out in May 2025. The subjects of this study were 23 class IIIB students, consisting of 16 men and 7 women. Data Collection techniques were in the form of observation, written test, and documentation. Before the action was carried out, the students' mathematical critical thinking ability was 22.72%, then in cycle I meeting I increased to 36,36%, cycle I meeting II increased to 77,27%. Furthermore, cycle II meeting I increased to 81,81%, and cycle II meeting II increased to 86,36%. It can be concluded that using the discovery learning approach can improve students' mathematical critical thinking ability in Mathematics subjects at UPT SDN 004 Salo.